Pentingnya Bahasa Indonesia dalam Pembentukan Karakter Anak Usia Dini - Fitrah, Nada Anugerah; Febriana, Ika; Putri, Aminati; Sitanggang, Nadia Febrian; Belinda, Jessica; Adriani, Karina Dinda; Julafni, Mia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia, as a country with diverse ethnicities and cultures, requires effective communication tools to maintain unity and nationalism among its citizens. Bahasa Indonesia plays an important role as a national identity and official communication tool, which is taught to children from an early age. Learning Bahasa Indonesia in Early Childhood Education (PAUD) not only aims to develop language skills, but also contributes to the formation of children's character. Through a qualitative approach and literature study, this study reveals that learning Bahasa Indonesia can shape children's character through four aspects of language: listening, speaking, reading, and writing. Ki Hajar Dewantara emphasized the importance of character education that is integrated with language learning, so that children can understand the norms and values that apply in society. The results of the study show that good language proficiency reflects a complete character, while poor language use can have a negative impact on the development of children's character. Therefore, the role of parents and educators is very important in instilling positive values through language, as well as creating an environment that supports the development of children's character. This study is expected to increase awareness of the importance of teaching Bahasa Indonesia as part of the formation of children's character from an early age.